A process evaluation of an on-line fall prevention and management program for individuals who use wheelchairs or scooters living with multiple sclerosis - Van Denend, Toni; Peterson, Elizabeth W.; McArthur, Amy Roder; Yarnot, Rebecca; Kish, Jacqueline; Steinkellner, Sydney; Sandhu, Arman; Rice, Laura A. (Frontiers in Public Health, 2022)
Background Falls and resulting injury are a significant concern for individuals living with multiple sclerosis (MS) that use a wheelchair and/or scooter to support mobility. Effective fall prevention efforts are vital to support the health, wellbeing, and participation for these individuals. Aims This study reports the findings from the process evaluation conducted in association with a pilot study evaluating the efficacy of Individualized Reduction of FaLLs-Online (iROLL-O), an online, group fall prevention, and management program specifically designed for community-based people living with multiple sclerosis (pwMS) who are full-time wheelchair or scooter users. Methods A mixed-methods process evaluation was conducted, with specific attention to the impact of online delivery on intervention implementation, participant satisfaction, and mechanisms of change (MOC). Multiple data sources were utilized, including post-session and post-intervention participant and trainer feedback forms and participant qualitative interview data. Descriptive analysis was conducted using Microsoft Excel. Close-ended questions were analyzed by examining five-point Likert scale responses. Qualitative interview data was explored using thematic analysis. Results Twelve participants and three trainers (one occupational therapist and two physical therapists) contributed to the study. Online delivery did not compromise session fidelity, which averaged 95%. No significant adaptations to the intervention were made during delivery. Participant satisfaction was high at 4.6/5.0. Post-course Trainer Feedback Forms indicate trainer satisfaction with the group dynamic, ability to address unique group needs, and program content. Reach improved with online delivery as transportation barriers were removed and recruitment from a broader geographic area was enabled. Three themes reflecting key MOC emerged from the analysis: group context, motivation for participant engagement, and the multifaceted nature of the program. The COVID-19 pandemic was identified as a contextual factor impacting community participation. Both participants and trainers identified the group dynamic as a strength. The trainers valued the program's flexibility in allowing them to address individual and/or group-specific fall prevention needs. Conclusion Feedback from key stakeholders was essential to a meaningful process evaluation. Online delivery supported program implementation, including reach, and resulted in high levels of satisfaction among participants and trainers. Future iterations should aim to uphold the positive group context, recruit, and train skilled interventionists who are licensed as occupational or physical therapists and continue to provide the program's diverse approach to fall prevention and management.